Neoantigen‐based cancer vaccination using chimeric RNA‐loaded dendritic cell‐derived extracellular vesicles. Issue 8 (4th August 2022) - Xiong, Xiao; Ke, Xiurong; Wang, Lu; Lin, Yusheng; Wang, Shuhong; Yao, Zhimeng; Li, Kai; Luo, Yichen; Liu, Fan; Pan, Yunlong; Yeung, Sai‐Ching J.; Helfrich, Wijnand; et al.
Abstract: Cancer vaccines critically rely on the availability of targetable immunogenic cancer‐specific neoepitopes. However, mutation‐based immunogenic neoantigens are rare or even non‐existent in subgroups of cancer types. To address this issue, we exploited a cancer‐specific aberrant transcription‐induced chimeric RNA, designated A‐Pas chiRNA, as a possible source of clinically relevant and targetable neoantigens. A‐Pas chiRNA encodes a recently discovered cancer‐specific chimeric protein that comprises full‐length astrotactin‐2 ( ASTN2 ) C‐terminally fused in‐frame to the antisense sequence of the 18 th intron of pregnancy‐associated plasma protein‐A ( PAPPA ). We used extracellular vesicles (EVs) from A‐Pas chiRNA‐transfected dendritic cells (DCs) to produce the cell‐free anticancer vaccine DEXA‐P . Treatment of immunocompetent cancer‐bearing mice with DEXA‐P inhibited tumour growth and prolonged animal survival. In summary, we demonstrate for the first time that cancer‐specific transcription‐induced chimeric RNAs can be exploited to produce a cell‐free cancer vaccine that induces potent CD8 + T cell‐mediated anticancer immunity. Our novel approach may be particularly useful for developing cancer vaccines to treat malignancies with low mutational burden or without mutation‐based antigens. Moreover, this cell‐free anticancer vaccine approach may offer several practical advantages over cell‐based vaccines, such as ease of scalability and genetic modifiability as well as enhanced shelf life.